Educational Process Quality from the Viewpoint of Future Innovators and Engineers - NADTOCHIY, Yuliya (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
A concept of ‘innovation’ is commonly used in today's world. Innovations have been created in all areas of life of society and often make our life comfortable. The innovator profession becomes relevant. Innovation is an area of specialization in the Russian educational institutions of higher education in which such specialists are trained. Engineer is another profession required to create (develop, design, etc.) various innovative technologies. The article examines the factors that influence the quality of modern educational process in the training of future innovators and engineers, based on the analysis of the results obtained during the student survey.